KADAR AIR DAN KARBOHIDRAT BERPERAN PENTING DALAM MEMPERTAHANKAN KUALITAS BENIH KARET - Rudi Hartawan; Yulistiati Nengsih (Agrovigor, 2012)
Determination of the main variables of seed quality is very important that the control variables can be done to the fullest. This issue has been addressed through a trial that aims to determine the main variables that affect the quality of the rubber seeds in storage. Experiment was conducted from April to August 2012 at the Basic Laboratory, The Batanghari University, Jambi and Center for Post Harvest Research and Development,  The Ministry of Agriculture, Bogor. The experimental design used was completely randomized design. The treatment were storage time as follows: S0 = control, 0 days of storage, S1 = 3 days of storage, S2 = 6 days of storage, S3 = 9 days of storage, and S4 = 12 days of storage, S5 = 15 days of storage, and S6 = 18 days of storage. Each treatment was repeated three times so that there are 21 experimental plots. In this study, experimental plots considered a seed lot. Each lot contained 60 of rubber seed. The results showed that 80% germination can only be maintained until day 9 with indicators respiration rate of 3.68 ml CO2 hr-1, water content of 40.25%, protein 23.45%, carbohydrate 23.15%, fat 24.76 %, and electric conductivity 80 μS cm-1 g-1. The main variables that maintain seed quality in storage is the water content and carbohydrate. Efforts to maintain the water content remains high should be done at a temperature of about 20oC due to low temperature will reduce the rate of respiration.